ANALISIS SISTEM DU PONT UNTUK MENILAI KINERJA KEUANGAN PERUSAHAAN (STUDI KASUS PADA PT ENSEVAL PUTERA MEGATRADING, TBK) - Meisaroh, Firda (Jurnal Ilmiah Mahasiswa FEB, 2012)
This study aims to determine the financial performance Enseval Putera Megatrading PT, Tbk., during the study period in 2007-2011. Return on Investment (ROI) is one of corporate profitability measurement instruments aimed at understanding corporate profitability ratio. The research method used in this study was descriptive quantitative method with Du Pont financial ratio formula. The result showed the decrease of both the ROI and Total Assets Turnover. The Total Assets Turnover did not only show the effectiveness in the management, but the high value could be caused by the depreciation of the old assets. Total Assets Turnover should be related with the profit margin in order to obtain Return on Investment. Keywords:       return on investment, du pont system, total assets turnover, net profit margin